Low Pressure Performances and Applications of Gas Chromatography Using Manganese Sulfate Crystal Hydrate as Stationary Phase - Tao, Yong; Fan, Changling (Asian Journal of Chemistry, 2012)
Combining of low pressure technology with manganese sulfate crystal hydrate as stationary phase in gas chromatography was realized. Experiments results showed that the performances of chromatography column in low pressure are greatly improved than that in standard atmospheric pressure. The maximum plate number of 2465 exists in the optimal pressure of 0.8 × 105 Pa. Under this pressure, the retention time decreases 18 % compared to standard atmospheric pressure. The theoretical height of plate is 0.74 mm, which much lower than the 0.90 mm. The efficiency of chromatography column is also improved under low pressure. The chromatography column still maintains its stability after the successive analysis of 60 d. The relative error and average recoveries of toluene are 2.22 % and 100.93 % when the column is applied to the analysis of toluene in xylene.